Assessing fairness of dynamic grid tariffs. (September 2017) - Neuteleers, Stijn; Mulder, Machiel; Hindriks, Frank
Abstract: The increase in the supply of intermittent renewable energy and the higher electricity use lead to stronger variation in network usage, which either requires costly network extensions or the implementation of incentives to reduce peaks. This paper focuses on the latter, namely dynamic tariffs. However, a tension may exist between economic arguments for dynamic pricing and people perceiving such pricing as unfair. This paper seeks to assess the fairness of dynamic tariffs through a combination of theoretical and empirical research. Fairness is defined broader than inequality; it is understood more objectively than just people's perceptions and thus requires engagement with ethical theory; and the fairness analysis is not only based on abstract ethical reflection but also on analysing the underlying arguments for people's perceptions. Both the theoretical fairness assessment and the survey among Dutch households reveal that dynamic tariffs are less fair than transport and capacity tariffs and fairer than Ramsey pricing. The fairness of dynamic tariffs depends on implementation conditions such as: clear, non-economic arguments as justification, guarantying basic-needs fulfilment, decreasing perception that 'peak use is only for the rich', and increasing predictability. Highlights: Methodology allows integrating economics, behavioural-economics and ethics. Integrated approach transcends tension between efficiency and perceived fairness. Assessment fairness of flat rate, transport charge, Ramsey pricing and peak pricing. Results survey of fairness perceptions grid tariffs among Dutch households. Conditions for increasing fairness of dynamic grid tariffs are specified.